Evaluating quasi-periodic variations in the γ-ray light curves of Fermi-LAT blazars - Ait Benkhali, Faical; Hofmann, Werner; Rieger, Frank M. (Astronomy and astrophysics, 2020)
The detection of periodicities in the light curves of active galactic nuclei (AGNs) could have profound consequences for our understanding of the nature and radiation physics of these objects. At high energies (HE; E > 100 MeV), five blazars (PG 1553+113, PKS 2155−304, PKS 0426−380, PKS 0537−441 and PKS 0301−243) have been reported to show year-like quasi-periodic variations (QPVs) with significance > 3σ. As these findings are based on only a few cycles, care needs to be taken to properly account for random variations that can produce intervals of seemingly periodic behavior.Aims. We present results of an updated timing analysis for six blazars (adding PKS 0447−439 to the above), using suitable methods to evaluate their long-term variability properties and to search for QPVs in their light curves.Methods. We generate γ-ray light curves covering almost ten years, study their timing properties, and search for QPVs using the Lomb-Scargle Periodogram and the Wavelet Z-transform. Extended Monte Carlo simulations are used to evaluate the statistical significance.Results. (1) Comparing their probability density functions, all sources (except PG 1553+113) exhibit a clear deviation from a Gaussian distribution, but are consistent with being log-normal, suggesting that the underlying variability is of a nonlinear, multiplicative nature. (2) Apart from PKS 0301−243, the power spectral density for all investigated blazars is close to flicker noise (power-law slope −1). (3) Possible QPVs with a local significance ≳3σ are found in all light curves (apart from PKS 0426−380 and PKS 0537−441), with observed periods in the range (1.7 − 2.8) yr. The evidence is strongly reduced however if evaluated in terms of a global significance.Conclusions. Our results advise caution as to the significance of reported year-like HE QPVs in blazars. Somewhat surprisingly, the putative redhift-corrected period all cluster around ∼1.6 yr. We speculate on possible implications for QPV generation.
Gesehen am 26.03.2020